Edukasi menumbuhkan dan meningkatkan kepercayaan diri siswa dalam meraih prestasi - Iskandar, Iskandar; Yoseva, Trifena (JOURNAL of Public Health Concerns, 2025)
Background: Self-confidence significantly contributes to student motivation in achieving academic success. Students need to recognize their potential, set goals, and develop and compete effectively in both academic and non-academic settings. Students with strong self-confidence can develop an independent character, as they can organize, design, and evaluate the learning process, both theoretically and practically. Purpose: To provide students with knowledge and understanding about developing and enhancing self-confidence in achieving success. Method: This community service activity was conducted at State Junior High School (SMPN) 22 Samarinda, class IXC, on Monday, April 21, 2025, from 10:00 AM to 12:00 PM WITA, in the Science Laboratory. Thirty-two students from class IXC participated in the activity. The material was delivered using a lecture method using projectors, laptops, and leaflets. The material presented was related to self-motivation and increasing self-confidence in achieving success. Measuring respondents' knowledge levels using a questionnaire with a one-group pre-test & post-test design, namely by providing a test before educational activities (pre-test) and a test after education (post-test). Results: Data obtained showed that the level of student knowledge before the educational activity (pre-test) was in the poor category for 11 students (34.4%) and in the good category for 21 students (65.6%). Meanwhile, the level of student knowledge after the educational activity (post-test) was in the poor category for 3 students (9.4%) and in the good category for 29 students (90.6%). Conclusion: Participatory and interactive educational activities directly with students are very effective in increasing students' knowledge and understanding of self-motivation. This increased knowledge also fosters students' self-confidence in achieving success. Suggestion: State Junior High School (SMPN) 22 Samarinda is expected to conduct self-motivational activities through seminars or training for students to foster and increase students' self-confidence in achieving success in any field. It is also hoped that parents, as the students' primary support and closest environment, can consistently provide encouragement and motivation to students to engage in positive activities so that they can develop their personality and academic achievement through self-confidence. Keywords: Achieving achievement; Education; Motivation; Self-Confidence; Students Pendahuluan: Sikap percaya diri memiliki kontribusi yang besar terhadap motivasi siswa dalam meraih prestasi di sekolah. Siswa perlu mengenali potensi diri, membuat target yang akan ditempuh dan mampu berkembang serta bersaing baik dalam dunia akademik maupun non akademik. Siswa dengan kepercayaan diri yang baik dapat menumbuhkan karakter yang mandiri, dikarenakan siswa dapat mengatur, merancang, dan mengevaluasi  proses  pembelajaran, baik dalam teori maupun praktik Tujuan: Memberikan pengetahuan dan pemahaman siswa tentang menumbuhkan dan meningkatkan tingkat kepercayaan diri dalam meraih prestasi Metode: Kegiatan pengabdian masyarakat ini dilaksanakan di Sekolah Menengah Pertama Negeri (SMPN) 22 Samarinda,  kelas IXC, pada hari Senin, 21 April 2025 pukul 10.00-12.00 Wita, tempat kegiatan di Laboratorium IPA. Jumlah peserta yang mengikuti kegiatan berjumlah 32 orang siswa kelas IXC. Penyampaian materi dengan metode ceramah menggunakan media proyektor, laptop, dan leaflet. Materi penyuluhan yang disampaikan terkait dengan motivasi diri dan meningkatkan kepercayaan diri dalam meraih prestasi. Pengukuran tingkat pengetahuan responden menggunakan kuesioner dengan one group pre-test & post-test design, yaitu dengan memberikan tes  sebelum kegiatan edukasi (pre-test) dan tes setelah edukasi (post-test). Hasil : Mendapatkan data bahwa tingkat pengetahuan siswa pada saat sebelum kegiatan edukasi (pre-test) adalah dalam kategori kurang sebanyak 11 orang (34.4%) dan dalam kategori baik sebanyak 21 orang (65.6%),  sedangkan tingkat pengetahuan siswa pada setelah kegiatan edukasi (post-test) menjadi dalam kategori kurang sebanyak 3 orang (9.4%) dan dalam kategori baik sebanyak 29 orang (90.6%). Simpulan: Kegiatan edukasi partisipatif dan interaktif langsung kepada siswa sangat efektif dalam meningkatkan pengetahuan dan pemahaman siswa tentang motivasi diri, sehingga dengan meningkatnya pengetahuan siswa juga menumbuhkan kepercayaan diri pada siswa dalam meraih prestasi.. Saran: Diharapkan kepada pihak SMP 22 Samarinda untuk dapat melakukan kegiatan berupa motivasi diri melalui seminar atau pelatihan kepada siswa untuk menumbuhkan dan meningkatkan tingkat kepercayaan diri siswa dalam meraih prestasi di bidang apapun. Diharapkan juga kepada orang tua yang merupakan dukungan utama siswa sebagai lingkungan terdekat, dapat selalu memberikan semangat dan motivasi kepada siswa untuk melakukan kegiatan yang positif sehingga dapat mengembangkan kepribadian dan prestasi belajar melalui rasa percaya diri.